The European Union Strategy for the Adriatic- Ionian Region: An Alternative to the European Integration in the Western Balkans? - Vasileios MIGKOS; Murat ÖNSOY (Gazi Akademik Bakış)
Despite the European Union (EU)-sponsored economic and political reforms, the Western Balkans has made little to no progress in several fields, including post-conflict reconciliation, post-socialist economic transformation, and democracy. This situation threatens both regional stability and, more importantly, the EU integration process in the region. On the other hand, the EU is in crisis and its enlargement policy has lost its momentum. If alternative policies are not put in place in the Western Balkans, it would once again be dragged into a whirlpool of conflict. This study asserts that the EU Strategy for Adriatic and Ionian Region (EUSAIR), which is a Macro-Regional Strategy could serve as a more realistic integration tool in the Western Balkans and an alternative for EU membership.